2017
DOI: 10.1142/s0218271817300245
|View full text |Cite
|
Sign up to set email alerts
|

Viscous cosmology for early- and late-time universe

Abstract: point of view the inclusion of viscosity concepts in the macroscopic theory of the cosmic fluid would appear most natural, as an ideal fluid is after all an abstraction (exluding special cases such as superconductivity). Making use of modern observational results for the Hubble parameter plus standard Friedmann formalism, we may extrapolate the description of the universe back in time up to the inflationary era, or we may go to the opposite extreme and analyze the probable ultimate fate of the universe. In thi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
137
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 206 publications
(149 citation statements)
references
References 248 publications
3
137
0
Order By: Relevance
“…As another example of the dark energy models, we may consider the viscous dark energy model (see [51] and the references therein) where a bulk viscosity in the cosmic fluid generates the accelerating expansion of the universe. In the viscous dark energy model, the conservation law of the fluid is modified by the bulk viscosity ζ as follows:…”
Section: Discussionmentioning
confidence: 99%
“…As another example of the dark energy models, we may consider the viscous dark energy model (see [51] and the references therein) where a bulk viscosity in the cosmic fluid generates the accelerating expansion of the universe. In the viscous dark energy model, the conservation law of the fluid is modified by the bulk viscosity ζ as follows:…”
Section: Discussionmentioning
confidence: 99%
“…[42][43][44][45][46][47][48][49][50]. Brevik et al [51] discussed the general account about viscous cosmology for early and late time universe. Norman and Brevik [52] analyze characteristic properties of two different viscous cosmology models for the future universe.…”
Section: Introductionmentioning
confidence: 99%
“…In recent times, the effect of bulk viscous matter in causing the late acceleration was analysed by many [8][9][10][11][12][13][14]. In a recent review, Brevik et al [15] have shown important implications and capabili-ties of viscosity in describing inflationary era and late time acceleration of the universe; see also Ref. [16].…”
Section: Introductionmentioning
confidence: 99%